2002
DOI: 10.1073/pnas.002024599
|View full text |Cite
|
Sign up to set email alerts
|

Complex pattern of Mycobacterium marinum gene expression during long-term granulomatous infection

Abstract: During latent infection of humans with Mycobacterium tuberculosis, bacteria persist in the asymptomatic host within granulomas, organized collections of differentiated macrophages, and other immune cells. The mechanisms for persistence remain poorly understood, as is the metabolic and replicative state of the microbes within granulomas. We analyzed the gene expression profile of Mycobacterium marinum, the cause of fish and amphibian tuberculosis, during its persistence in granulomas. We identified genes expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
72
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(74 citation statements)
references
References 43 publications
1
72
1
Order By: Relevance
“…This strengthens their association with host granuloma formation. Our in vivo pulmonary TB granuloma-associated M. tuberculosis-expressed genes did not overlap with the granulomaassociated genes or macrophage-associated genes described by Ramakrishnan and colleagues (61,62) for M. marinum, which might be due to differences between the mycobacterial species studied. Moreover, several of the IVE-TB genes we identified to be highly expressed have also been described previously, including Rv0467 (icl), which encodes an enzyme in the glyoxylate pathway, which is important for M. tuberculosis persistence of M. tuberculosis (63,64), and Rv0991c, which is part of the so-called in vivo-expressed genomic island (20).…”
Section: Discussionmentioning
confidence: 70%
“…This strengthens their association with host granuloma formation. Our in vivo pulmonary TB granuloma-associated M. tuberculosis-expressed genes did not overlap with the granulomaassociated genes or macrophage-associated genes described by Ramakrishnan and colleagues (61,62) for M. marinum, which might be due to differences between the mycobacterial species studied. Moreover, several of the IVE-TB genes we identified to be highly expressed have also been described previously, including Rv0467 (icl), which encodes an enzyme in the glyoxylate pathway, which is important for M. tuberculosis persistence of M. tuberculosis (63,64), and Rv0991c, which is part of the so-called in vivo-expressed genomic island (20).…”
Section: Discussionmentioning
confidence: 70%
“…1A). For example, the map24 promoter is responsive to low pH (15), and the screen identified three components of the vacuolar ATPase (V-ATPase), consistent with the hypothesis that depletion of the V-ATPase results in an increase in the phagosomal pH and, hence, diminished map24 induction. We anticipated that there might be additional factors that result in altered map24 promoter activity without affecting intracellular growth (possibilities b versus c in Fig.…”
Section: Resultsmentioning
confidence: 57%
“…These bacteria constitutively express dsRed2 under control of the msp12 promoter, whereas GFP is expressed under control of the map49 promoter (26). map49 is induced during intracellular growth, but, unlike map24, the stimulus does not appear to be low pH (15). When ESCRT I-depleted cells were infected with the dual reporter bacteria, we found diminished GFP expression.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…We considered this an important question to address, as there exists a large body of data suggesting a role for Ald in the in vivo persistence of mycobacteria. The ald gene is up-regulated by M. tuberculosis under hypoxic conditions or nutrient starvation in broth culture (4,23), and by M. marinum during persistent granulomatous infection of frogs (5). Studies by Chen and colleagues demonstrated that the lack of Ald activity by BCG inhibits growth in the presence of alanine, suggesting loss of Ald activity may limit the in vivo persistence of BCG (6).…”
mentioning
confidence: 99%